Sovereign Rents and the Quality of Tax Policy and Administration - Knack, Stephen (World Bank, Washington, DC, 2012)
The availability of windfall revenues from natural resource exports or foreign aid potentially weakens governments' incentives to design efficient tax systems. Cross-country data for developing countries provide evidence for this hypothesis, using a World Bank indicator of "efficiency of revenue mobilization." Aid's negative effects on the quality of tax systems are robust to correcting for potential reverse causality, to changes in the sample, and to alternative estimation methods. Fuel export revenues are also associated with lower-quality tax policy and administration, but this finding is somewhat sensitive to outliers. Non-fuel resource exports, in contrast, show no relationship to the efficiency of revenue mobilization.